Evaluation of Serum Transaminases Levels In Transfused β-Thalssaemia Major Patients - Mustafa, Saad A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: β-thalassemia major is a genetic disorder characterized by reduced rate of β-globin chain production. Clinically, β-thalassemia major is a severe, transfusion-dependant disorder; repeated blood transfusion will lead eventually to chronic liver disease. Patients and Methods: One hundred patients ; 56 males and 44 females who were known cases with β-thalassemia major on regular blood transfusion, aged between 6 months and 18 years, were studied in a private pathology laboratory, between January 2002-January 2006.Blood was drawn to estimate serum glutamic pyruvate transaminase (SGPT) and serum glutamic oxaloacetic transaminase (SGOT) levels. Results: Sixty-six patients (66%) had elevated SGPT and SGOT levels ranging between two and more than five fold increase than normal.Thirty-four patients (34%) had normal SGPT and SGOT values of less than 40 i.u. /L. The levels of SGPT and SGOT were significantly higher in splenectomised patients than nonsplenectomised. Conclusion: Serum transaminases were elevated in (66%) of transfused patients with B-thalassemia major.